2018
DOI: 10.1016/j.chemosphere.2017.11.158
|View full text |Cite
|
Sign up to set email alerts
|

Nano-litter from cigarette butts: Environmental implications and urgent consideration

Abstract: Cigarette butts (CGB) are equivalent to plastic litter in terms of number of pieces released directly into the environment. Due to their small size and social use, CGB are commonly found in natural systems, and several questions have been raised concerning the contaminants that are released with CGB, including metals, organic species, and nanoparticles. The aim of the present study is to investigate the release of nanoscale particles from CGB by leaching with rainwater. After seven days of passive stirring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…This publication is available free of charge from: https://doi.org/10.6028/NIST.IR.8256 To study the influence of rainwater saturation on emissions from cigarette butts, freshly smoked cigarette butts were preconditioned before being placed into dark chambers (Experiments 5 and 6 in Table 2.4). An artificial rainwater concentrate solution previously used for cigarette butt aqueous leaching experiments (Chevalier et al 2018) was prepared by dissolving the following components in 1 L of distilled water: NaCl (3.24 g), KCl (0.36 g), CaCl2•2H2O (1.65 g), (NH4)2SO4 (3.41 g), MgSO4•7H2O (2.98 g), and NaNO3 (4.08 g). Following Chevalieret al (2018), the solution was then diluted by a factor of 1000 prior to use.…”
Section: Spherementioning
confidence: 99%
See 1 more Smart Citation
“…This publication is available free of charge from: https://doi.org/10.6028/NIST.IR.8256 To study the influence of rainwater saturation on emissions from cigarette butts, freshly smoked cigarette butts were preconditioned before being placed into dark chambers (Experiments 5 and 6 in Table 2.4). An artificial rainwater concentrate solution previously used for cigarette butt aqueous leaching experiments (Chevalier et al 2018) was prepared by dissolving the following components in 1 L of distilled water: NaCl (3.24 g), KCl (0.36 g), CaCl2•2H2O (1.65 g), (NH4)2SO4 (3.41 g), MgSO4•7H2O (2.98 g), and NaNO3 (4.08 g). Following Chevalieret al (2018), the solution was then diluted by a factor of 1000 prior to use.…”
Section: Spherementioning
confidence: 99%
“…Free-base nicotine is the dominant form of nicotine on the cigarette filter when freshly smoked, although the pH and nicotine species can change with environmental exposures. The artificial rainwater solution has been measured by Chevalier et al (2018) to have a pH of 5.2, indicating that most of the nicotine in the aqueous phase is likely to be in the non-volatile monopronated form. Nicotine is also fairly water soluble, so a significant amount of nicotine in the wet filters and butts would likely disolve into the aqueous phase and then protonate, making it non-volatile.…”
Section: Influence Of Water Saturationmentioning
confidence: 99%
“…demonstrated that nanoparticles with sizes ranging from 6 nm to 50 nm from cigarette smoke are generally transferred to humans, i.e., not retained by the cigarette filter (van Dijk et al, 2011). Other studies showed that a smoked CGB releases soot particles larger than 70 nm into aqueous systems (Chevalier et al, 2018). There is a fairly remarkable difference in the abilities of filters to absorb nanoparticles in water versus air.…”
Section: Filter Influencementioning
confidence: 99%
“…It is estimated that more than 750 000 metric tons of CGBs end up as litter worldwide per year, which corresponds to approximately 4.5 10 12 CGB units released into our environment each year (Novotny and Slaughter, 2014). Because CGBs are composed of cellulose acetate, they can interact with several organic and metallic pollutants in the environment (Chevalier et al, 2018). Pu et al recently demonstrated that CGB based-materials act as a powerful Uranium sorbent (106 mg g -1 ) (Pu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Discarded cigarette butts (DCBs) commonly referred to as "cigarette butts" are one of the most littered items globally (Chevalier, et al, 2018, Rebischung, et al, 2018. DCBs are mainly deposited in terrestrial and aquatic habitats, where they pose a serious threat to the A C C E P T E D M A N U S C R I P T environment due to their inability to easily biodegrade, and the presence of many trapped toxic agents in the filters after usage.…”
Section: Introductionmentioning
confidence: 99%